Hybridization With an Invasive Plant of Xanthium strumarium Improves the Tolerance of Its Native Congener X. sibiricum to Cadmium - Xue, Chenyang; Gao, Yingmei; Qu, Bo; Tai, Peidong; Guo, Cheng; Chang, Wenyue; Zhao, Guanghui (Frontiers in Plant Science, 2021)
Hybridization is one of the important factors influencing the adaptive evolution of invasive plants. According to previous studies, hybridization with an invasive plant reduces the adaptability of its native congener to environment. However, in this study, the hybridization with an invasive plant of Xanthium strumarium (LT) improves the tolerance and accumulation of its native congener X. sibiricum (CR) to cadmium (Cd). Under Cd stress, X. sibiricum♀×X. strumarium♂ (ZCR) showed higher biomass and Cd accumulation. Compared with CR, ZCR has longer vegetative and reproductive growth time. Moreover, ZCR adopted more reasonable biomass allocation strategy. ZCR increased the proportion of reproductive allocation and ensured its own survival with the increase of Cd stress. Furthermore, ZCR increased the translocation of Cd to aboveground parts and changed the distribution of Cd. A large amount of Cd is stored in senescent leaves and eliminated from the plant when the leaves fall off, which not only reduces the Cd content in the plant, but also reduces the toxicity of Cd in the normal leaves. Transcriptome analysis shows a total of 2055 (1060 up and 995 down) differentially expressed genes (DEGs) were detected in the leaves of Cd-stressed ZCR compared with CR, while only 792 (521 up and 271 down) were detected in X. strumarium♀×X. sibiricum♂ (ZLT) compared with LT. A large number of DGEs in ZCR and ZLT are involved in abscisic acid (ABA) synthesis and signal transduction. The genes induced by ABA in ZCR, including CNGC5/20，CPK1/28, CML, PTI3, RBOHC and WRKY33 were found differentially expressed compared CR. CCD4, NCED1/2, PSY2 and CYP707A involved in ABA synthesis and decomposition in ZLT were found differentially expressed compared LT. We speculated that ABA played an important role in Cd transportation of hybrids and Cd distribution in senescent and normal leaves. The results demonstrate that hybridization with an invasive plant improves the adaptability of the hybrid to Cd stress and may enhance the extinction risk of native congener in pollution environment.